GPD1L downregulation in colorectal cancer: a novel obesity-related biomarker linking metabolic dysregulation to tumor progression - Zhu, Feng; Li, Huiyuan; Liu, Hongzhang; Wang, Yusheng (Frontiers in Oncology, 2025)
ObjectiveTo delineate the expression profile and tumor-suppressive function of the metabolism-associated gene GPD1L in colorectal carcinogenesis. Methods: Transcriptomic datasets from TCGA and GEO repositories (GSE74602, GSE113513, GSE164191) were computationally analyzed. Paired tumor/adjacent mucosal specimens (n=58) from CRC patients at Jincheng People’s Hospital were analyzed alongside the NCM460 colon epithelial line and five CRC lines (SW620, HCT116, SW480, DLD-1, LOVO). Following GPD1L quantification via qPCR, selected cell models underwent pcDNA3.1-GPD1L transfection for functional characterization. Then Western blot analysis was used to explore its possible mechanism.ResultsComparative analysis revealed a marked elevation of GPD1L expression in non-neoplastic tissues relative to tumor specimens (P<0.001). Transcriptional profiling further identified significant depletion of GPD1L mRNA levels across malignant cell lines versus the NCM460 epithelial reference (P<0.05), with HCT116/SW620 showing maximal downregulation. Ectopic GPD1L expression attenuated oncogenic phenotypes: proliferation decreased (P<0.001), while Transwell quantification revealed 46.0% (HCT116: 605.0 ± 9.2 vs 326.7 ± 8.50 cells/field) and 54.3% (SW620: 455.3 ± 17.2 vs 208.0 ± 14.0 cells/field) reductions in migratory capacity (both P<0.001). Invasion assays showed parallel inhibition (HCT116: 43.3% decrease, P<0.01; SW620: 54.8% decrease, P<0.001). After overexpression of GPD1L, the expression levels of HIF-1α and MMP9 were reduced (P<0.05).ConclusionGPD1L downregulation represents a hallmark of CRC progression, with affecting the expression of HIF-1α and MMP9 significantly impeding malignant behaviors, nominating it as a candidate tumor suppressor in colorectal neoplasia.